2016
DOI: 10.1111/jar.12291
|View full text |Cite
|
Sign up to set email alerts
|

Improving Quality of Life Outcomes in Supported Accommodation for People with Intellectual Disability: What Makes a Difference?

Abstract: Background The quality of life (QOL) of people with intellectual disability living in supported accommodation services is variable, influenced by many possible factors. Various frameworks have attempted to identify these factors without assigning value, direction of influence or relative impact on outcomes. Methods A realist review of the literature aimed to expose different propositions about variables influencing QOL outcomes and review the strength of supporting evidence for these, to identify their relativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
109
0
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 100 publications
(117 citation statements)
references
References 99 publications
3
109
0
5
Order By: Relevance
“…As already noted, research has generally found that active support is key to both achieving better outcomes for those receiving support and in making it easier to implement other elements of person‐centred support such as effective communication, positive behaviour support and the provision of autism friendly environments (Beadle‐Brown et al., ; Bigby & Beadle‐Brown, ; Bradshaw et al., ; Mansell & Beadle‐Brown, ; Stancliffe et al., ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…As already noted, research has generally found that active support is key to both achieving better outcomes for those receiving support and in making it easier to implement other elements of person‐centred support such as effective communication, positive behaviour support and the provision of autism friendly environments (Beadle‐Brown et al., ; Bigby & Beadle‐Brown, ; Bradshaw et al., ; Mansell & Beadle‐Brown, ; Stancliffe et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…Although living in ordinary housing dispersed in the community is a necessary condition for improved quality of life (such as inclusion, independence, self‐determination, well‐being), it is not sufficient (Mansell, ). Apart from the severity of disability and the presence of complex needs, only one factor has emerged from the research as predicting quality of life of those with intellectual and developmental disabilities—whether those services are providing a facilitative style of support that focuses on enabling and empowering people with disabilities (See Bigby & Beadle‐Brown, for a recent review). One approach for providing such support, and the one with the most research, is usually referred to as [person‐centred] active support (Mansell & Beadle‐Brown, ; Stancliffe, Jones, Mansell, & Lowe, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, despite many other hypotheses about what supports implementation and maintains good active support, most notably the role of culture, there is very little research exploring these (Bigby & Beadle-Brown, 2016). The ongoing project from which the data in this paper are drawn is attempting to fill that gap by exploring the organisational factors that impact on implementation and maintenance of active support.…”
mentioning
confidence: 99%
“…The evidence base spans four decades, involves at least 1400 people, uses different methodologies, in different countries, in different settings and involves different research teams and training approaches. Studies of effectiveness have ranged from small-scale pre-post training comparisons through to larger scale observational studies (see Bigby & Beadle-Brown, 2016;Jones, Felce, Lowe, Bowley, Pagler, Gallagher, et al, 2001;Jones, Felce, Lowe, Bowley, Pagler, Strong, et al, 2001;.…”
mentioning
confidence: 99%